2018
DOI: 10.1183/23120541.00120-2017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of next treatment received after nivolumab progression in patients with advanced nonsmall cell lung cancer

Abstract: Nivolumab for the treatment of advanced nonsmall cell lung cancer (NSCLC) evaluated in phase III trials showed 50% progression at first evaluation, but better overall survival (OS), suggesting regained efficacy of treatments given thereafter. We aimed to evaluate the efficacy of nivolumab and of next treatment received after nivolumab progression in patients with advanced NSCLC.Our multicentre retrospective study included all patients receiving nivolumab between January and December 2015. The primary end-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 17 publications
(24 reference statements)
2
20
0
1
Order By: Relevance
“…The authors of most studies compared progressor's clinical and biological characteristics to those of responders. Our findings are consistent with those of other studies . Shiroyama et al found ECOG PS and inflammation to be factors associated with RP, whereas, according to Costantini et al's very recent publications, RP was significantly associated with ECOG PS, bone metastases or short duration of pre‐ICI treatment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The authors of most studies compared progressor's clinical and biological characteristics to those of responders. Our findings are consistent with those of other studies . Shiroyama et al found ECOG PS and inflammation to be factors associated with RP, whereas, according to Costantini et al's very recent publications, RP was significantly associated with ECOG PS, bone metastases or short duration of pre‐ICI treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The RP definition varies according to authors. Some base it on the tumor‐doubling time, whereas others rely on death occurring within the 3 months following ICI onset or ≥3 nivolumab infusions . Constantini et al considered patients to have refractory NSCLCs when their disease progressed after one or two nivolumab injections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested that treatment with immunotherapy does not condition the efficacy of subsequent chemotherapy. On the contrary, these studies seem to suggest an increase in the efficacy of chemotherapy [40][41][42][43][44], particularly when combined with anti-angiogenic agents [45][46][47], when administered after treatment with immunotherapy. Synergistic activity in both preclinical [48,49] and clinical models [21,22,25,26] support a hypothesis of a possible chemosensitization after prior exposure to immunotherapy.…”
Section: Discussionmentioning
confidence: 90%